Strain-dependent effects of clinical echovirus 30 outbreak isolates at the blood-CSF barrier - Dahm, Tobias; Morozov, Vasily; Hansman, Grant S.; Weiß, Christel; Stump-Guthier, Carolin; Schroten, Horst; Schwerk, Christian; Tenenbaum, Tobias; Rudolph, Henriette (Journal of neuroinflammation, 2018)
Echovirus (E) 30 (E-30) meningitis is characterized by neuroinflammation involving immune cell pleocytosis at the protective barriers of the central nervous system (CNS). In this context, infection of the blood-cerebrospinal fluid barrier (BCSFB), which has been demonstrated to be involved in enteroviral CNS pathogenesis, may affect the tight junction (TJ) and adherens junction (AJ) function and morphology.